PROTAC-Based Antivirals for Respiratory Viruses: A Novel Approach for Targeted Therapy and Vaccine Development - Amith Anugu; Pankaj Singh; Dharambir Kashyap; Jillwin Joseph; Sheetal Naik; Subhabrata Sarkar; Kamran Zaman; Manpreet Dhaliwal; Shubham Nagar; Tanishq Gupta; Prasanna Honnavar (Microorganisms)
The global burden of respiratory viral infections is notable, which is attributed to their higher transmissibility compared to other viral diseases. Respiratory viruses are seen to have evolved resistance to available treatment options. Although vaccines and antiviral drugs control some respiratory viruses, this control is limited due to unexpected events, such as mutations and the development of antiviral resistance. The technology of proteolysis-targeting chimeras (PROTACs) has been emerging as a novel technology in viral therapeutics. These are small molecules that can selectively degrade target proteins via the ubiquitin–proteasome pathway. PROTACs as a therapy were initially developed against cancer, but they have recently shown promising results in their antiviral mechanisms by targeting viral and/or host proteins involved in the pathogenesis of viral infections. In this review, we elaborate on the antiviral potential of PROTACs as therapeutic agents and their potential as vaccine components against important respiratory viral pathogens, including influenza viruses, coronaviruses (SARS-CoV-2), and respiratory syncytial virus. Advanced applications of PROTAC antiviral strategies, such as hemagglutinin and neuraminidase degraders for influenza and spike proteins of SARS-CoV-2, are detailed in this review. Additionally, the role of PROTACs in targeting cellular mechanisms within the host, thereby preventing viral pathogenesis and eliciting an antiviral effect, is discussed. The potential of PROTACs as vaccines, utilizing proteasome-based virus attenuation to achieve a robust protective immune response, while ensuring safety and enhancing efficient production, is also presented. With the promises exhibited by PROTACs, this technology faces significant challenges, including the emergence of novel viral strains, tissue-specific expression of E3 ligases, and pharmacokinetic constraints. With advanced computational design in molecular platforms, PROTAC-based antiviral development offers an alternative, transformative path in tackling respiratory viruses.